2012
DOI: 10.1063/1.4722929
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit field switching of magnetization in ferromagnetic films with perpendicular anisotropy

Abstract: As an alternative to conventional magnetic field, the effective spin-orbit field in transition metals, derived from the Rashba field experienced by itinerant electrons confined in a spatial inversion asymmetric plane through the s-d exchange interaction, is proposed for the manipulation of magnetization. Magnetization switching in ferromagnetic thin films with perpendicular magnetocrystalline anisotropy can be achieved by current induced spin-orbit field, with small in-plane applied magnetic field. Spin-orbit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Until now, the role of FLT in SOT switching is remain vague. Recent works have pointed out that the FLT can be much larger than SLT in some material combinations and it is possible to use FLT to switch the magnetization [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the role of FLT in SOT switching is remain vague. Recent works have pointed out that the FLT can be much larger than SLT in some material combinations and it is possible to use FLT to switch the magnetization [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Besides GHz magnetic field, local injection of high density current [30] can also initiate magnetization oscillation through the STT effect. Elastic waves [31] and spin-orbit field [32] in properly engineered material systems can serve as alternative means to locally exciting SWs that subsequently propagate to activate DWM.…”
mentioning
confidence: 99%
“…Current-induced SOT is often explained in terms of the field-like and the Slonczewski torques [1,7,23]. Recent experimental studies [24][25][26][27][28] found that the fieldlike torque can be much larger than the Slonczewski torque in some material combinations, and this field-like torque is also capable of switching the magnetization [29]. Here, we investigate the potential of SOT switching in the case where the field-like torque is predominant and combined with the Slonczewski torque.…”
Section: Introductionmentioning
confidence: 99%